The Level of 8-OHdG Serum was Higher in Women with Blighted Ovum - I Made Mahadinata Putra; I Gede P Surya (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To determine the difference of 8-hydroxy-2-deoxyguanocyne (8-OHdG) serum level in women experiencing blighted ovum and women with normal pregnancy. Method: This was a cross sectional study with 82 samples, divided into two groups. Thirty two cases of blighted ovum and 51 cases of normal pregnancies, with 7-12 weeks gestational age. The examination of 8-OHdG serum level, was performed with the venous blood taken from the cubiti veins, and its 8-OHdG serum quantities were than examined at the Pathology Lab. at Sanglah General Hospital. Data was analyzed with the Shapiro Wilk Test and the t independent test with alpha 0.05. Result: The average 8-OHdG serum level in women with blighted ovum and normal pregnancies were 0.177 (SD 0.06) ng/ml and 0.111 (SD 0.01)ng/ml, and significantly different (p<0.05). The cut off value of 8-OHdG serum level was 0.138 ng/ml with sensitivity of 96.1% and specificity of 80.6%. Conclusion: The level of 8-OHdG serum was higher in women with blighted ovum than in women with normal pregnancies. Keywords: 8-OHdG serum level, blighted ovum, and normal pregnancy.